Creative communities art works in economic development - Rushton, Michael, 1959- (Brookings Institution Press, 2013)
"Examines the impacts of arts and cultural consumption and production on local economies. Topics include location choices of arts entrepreneurs; links between the arts and non-arts sectors; public policies to foster local arts; and the arts' effects on incomes in cities across the United States and the United Kingdom"--Provided by publisher.